Digestibility and palatability of isolated porcine protein in dogs - Fabiane Yukiko Murakami; Daniele Cristina de Lima; Camilla Mariane Menezes Souza; Gislaine Bill Kaele; Simone Gisele de Oliveira; Ananda Portella Félix (Italian Journal of Animal Science, 2018)
The objective of this study was to evaluate the digestibility and palatability of an isolated porcine protein (IPP) for adult dogs. In the digestibility assay, eight adult Beagle dogs were distributed in a double Latin square (4 × 4) experimental design. Diets containing 0, 100, 200, or 300 g IPP/kg were offered. Diets (0–300 g IPP/kg) presented 229.6–265.3 g/kg crude protein (CP) and 17.59–18.73 MJ/kg metabolisable energy (ME). The apparent total tract digestibility (ATTD) of diets and of the IPP were evaluated by analysis of regression. For the palatability test, diets containing 0 and 300 g IPP/kg were compared using 16 adult dogs. Dry matter (DM) and CP ATTD and the ME content of the IPP were determined as 99.2%, 86.4% and 22.48 MJ/kg, respectively. Faecal DM (424–342 g/kg) and pH (6.86–5.98) were linearly reduced (p < .01) as dietary IPP increased. The other evaluated faecal characteristics were not influenced by the treatments (p > .05). Lower intake ratio was obtained with the diet with 300 g IPP/kg, compared with the diet with 0 g IPP/kg (p < .01). The inclusion of IPP in the diet increases the digestibility of dietary nutrients and ME content; however, it reduces food palatability and faecal DM. Isolated porcine protein presents high nutrient digestibility and ME content for dogs.